Artificial intelligence large language model ChatGPT: is it a trustworthy and reliable source of information for sarcoma patients? - Valentini, Marisa; Szkandera, Joanna; Smolle, Maria Anna; Scheipl, Susanne; Leithner, Andreas; Andreou, Dimosthenis (Frontiers in Public Health, 2024)
Introduction Since its introduction in November 2022, the artificial intelligence large language model ChatGPT has taken the world by storm. Among other applications it can be used by patients as a source of information on diseases and their treatments. However, little is known about the quality of the sarcoma-related information ChatGPT provides. We therefore aimed at analyzing how sarcoma experts evaluate the quality of ChatGPT’s responses on sarcoma-related inquiries and assess the bot’s answers in specific evaluation metrics. Methods The ChatGPT responses to a sample of 25 sarcoma-related questions (5 definitions, 9 general questions, and 11 treatment-related inquiries) were evaluated by 3 independent sarcoma experts. Each response was compared with authoritative resources and international guidelines and graded on 5 different metrics using a 5-point Likert scale: completeness, misleadingness, accuracy, being up-to-date, and appropriateness. This resulted in maximum 25 and minimum 5 points per answer, with higher scores indicating a higher response quality. Scores ≥21 points were rated as very good, between 16 and 20 as good, while scores ≤15 points were classified as poor (11–15) and very poor (≤10). Results The median score that ChatGPT’s answers achieved was 18.3 points (IQR, i.e., Inter-Quartile Range, 12.3–20.3 points). Six answers were classified as very good, 9 as good, while 5 answers each were rated as poor and very poor. The best scores were documented in the evaluation of how appropriate the response was for patients (median, 3.7 points; IQR, 2.5–4.2 points), which were significantly higher compared to the accuracy scores (median, 3.3 points; IQR, 2.0–4.2 points; p = 0.035). ChatGPT fared considerably worse with treatment-related questions, with only 45% of its responses classified as good or very good, compared to general questions (78% of responses good/very good) and definitions (60% of responses good/very good). Discussion The answers ChatGPT provided on a rare disease, such as sarcoma, were found to be of very inconsistent quality, with some answers being classified as very good and others as very poor. Sarcoma physicians should be aware of the risks of misinformation that ChatGPT poses and advise their patients accordingly.